A COMPARATIVE STUDY BETWEEN EXTENSIVE AND INTENSIVE READING IN EXPANDING VOCABULARY MASTERY: THEORETICAL STUDY (ELang | An English Language Education Journal, 2023)
This paper describes the comparative study between extensive and intensive reading approaches in expanding vocabulary mastery. It is presented in theoretical study based on experiences, literature review, and references, and followed by interpretation. In extensive reading approach, the teacher provides a lot of reading books for students; calls the students to choose the book that they want to read based on their interest and needs. The teacher asks the students to retell the content of the book in general after reading or write a book report based on their own words and asks them to do vocabulary tasks such as identifying part of speech and translate the meaning of the target words, and the teacher review of unfamiliar or target words that students found before. In contrast, intensive reading focuses on getting students to concentrate on exact meaning. Besides, intensive reading provides short texts are used to learn new vocabulary. In intensive reading, the teacher asked some questions related to the topic given and distributed reading text to the students. The teacher also asked the students to read the whole text intensively. Based on the theoretical study, the extensive reading thus expands more significantly the vocabulary mastery than intensive reading.